2023
DOI: 10.3389/fnut.2023.1000326
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic values of the prognostic nutritional index, geriatric nutritional risk index, and systemic inflammatory indexes in patients with stage IIB–III cervical cancer receiving radiotherapy

Abstract: BackgroundGrowing evidence suggests that nutritional status and inflammation are associated with survival in various cancers. This study aimed to evaluate the prognostic value of the prognostic nutritional index (PNI), geriatric nutritional risk index (GNRI), and systemic inflammatory indexes (neutrophil/lymphocyte ratio [NLR], monocyte/lymphocyte ratio [MLR], and platelet/lymphocyte ratio [PLR]) in patients with stage IIB–III cervical cancer receiving radiotherapy.ResultsThe ideal cutoff values for the PNI, G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 64 publications
1
9
0
Order By: Relevance
“…In addition, low GNRI predicted poor outcome in many cancers. In Wang’s study, GNRI was identified as a significant prognostic factor for OS and PFS in cervical cancer ( 49 ). A meta-analysis with 11 studies also showed that GNRI has good prognostic ability on OS (HR 1.96) in patients with non-small cell lung cancer ( 50 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, low GNRI predicted poor outcome in many cancers. In Wang’s study, GNRI was identified as a significant prognostic factor for OS and PFS in cervical cancer ( 49 ). A meta-analysis with 11 studies also showed that GNRI has good prognostic ability on OS (HR 1.96) in patients with non-small cell lung cancer ( 50 ).…”
Section: Discussionmentioning
confidence: 99%
“…For below-knee amputations, nutrition plays an important role in both the success of the treatment and quality of life quality. [ 15 17 ] In the research conducted In the literature, there has been no study related to PNI after below-knee amputation. However, cardiovascular and cancer studies have suggested its prognostic value for PNI.…”
Section: Discussionmentioning
confidence: 99%
“…[ 16 ] It is also argued to be an indicator of the quality of life of patients. [ 17 ] Nutrition is an important treatment and quality of life indicator in below-knee amputation, cancer, and other cardiovascular diseases. In this respect, PNI may have prognostic value, especially for mortality in below-knee amputations.…”
Section: Introductionmentioning
confidence: 99%
“…Haraga et al found that low PNI predicted poor prognosis in LACC patients undergoing CRT and RT [ 19 ]. In another study, Wang et al supported the importance of PNI and systemic inflammatory indexes as predictors of prognosis in patients with stage IIB-III LACC receiving RT [ 20 ]. Furthermore, Guo et al demonstrated that a low PNI was associated with lower quality of life, reduced tolerance to RT and CHT, lower objective response rates, and worse OS for LACC [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, many of these studies have mainly focused on just one anthropometric parameter [ 16 , 17 , 18 ] or a limited set of such indices [ 13 , 19 , 20 , 21 ]. Furthermore, the impact of SO in LACC has not been previously evaluated and several studies did not thoroughly examine potential confounding variables [ 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%